Klimawandel und Soziale Arbeit - Dirk Wassermann (IU Internationale Hochschule, 2021)
– Climate change is a globally discussed and increasingly urgent topic; it is more and more responsible for wars, femicides, refugee movements and zoonoses worldwidely. Consequences will affect billions of people; many scientific disciplines recognise the importance of climate policy and its multiple consequences - but this issue didn't arrive in social work. In fact, in politics and the public, however, walls and fences, resistance and procrastination obviously dominate any approach of sustainable policy. "Human rights profession social work" - where are you??? Given that, discourses in economics or about a decoupling of resource consumption and productivity are running without social work. Yet it was just social work, which taught us how major processes of social change - including sustainable development - may succeed. Like no other, social work is transdisciplinary and present in all social settings. Only social work may combine global and local perspectives, science, policy and social life, moderate and connect different interests, implement common ideas into settings on the spot, as a base of global sustainability and justice. For this, new forms of cooperation between civil society, public administration and universities of applied sciences are requested.
urn:nbn:de:101:1-2021121009151361181301
Keywords: 300; Climate Change; Human Rights Profession Social Work; Sustainable Development; Global and Local Perspectives; Civil Society; Public Administration; Universities of Applied Sciences